2020
DOI: 10.3390/cells9061531
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage Differentiation for Formation of Innervated Skeletal Muscle Fibers from Healthy and Diseased Human Pluripotent Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) obtained by reprogramming primary somatic cells have revolutionized the fields of cell biology and disease modeling. However, the number protocols for generating mature muscle fibers with sarcolemmal organization using iPSCs remain limited, and partly mimic the complexity of mature skeletal muscle. Methods: We used a novel combination of small molecules added in a precise sequence for the simultaneous codifferentiation of human iPSCs into skeletal muscle cells and motor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…In particular, the NMJ pathophysiology in DMD is poorly studied and has the potential to be studied in hiPSC-derived tissues. The generation of multi-cellular 3D muscle tissues holds promise for studying complex tissue interactions in healthy and diseased states (Maffioletti et al, 2018;Mazaleyrat et al, 2020). Overall, the iPSCderived disease models have significant potential for generating personalized medicine platforms, disease specific drug screening, and studying pathogenic cellular or organ-organ crosstalk in a modular fashion.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…In particular, the NMJ pathophysiology in DMD is poorly studied and has the potential to be studied in hiPSC-derived tissues. The generation of multi-cellular 3D muscle tissues holds promise for studying complex tissue interactions in healthy and diseased states (Maffioletti et al, 2018;Mazaleyrat et al, 2020). Overall, the iPSCderived disease models have significant potential for generating personalized medicine platforms, disease specific drug screening, and studying pathogenic cellular or organ-organ crosstalk in a modular fashion.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…However, maintaining hiPSC-MNs in culture for more than 30 days is very challenging, because of cells detaching from their support. On the other hand, it is well known that MNs and muscle cells have mutual stabilizing and supportive influence to each other(Maffioletti et al, 2018; Mazaleyrat et al, 2020; Yoshida et al, 2015), and therefore, we sought to increase the viability and functionality of our hiPSC-MNs by coculturing them with mouse myoblasts (C2C12) for 7-9 days. This allowed obtaining large multinucleated myotubes, and hiPSC-MNs extending long neurites alongside the myotubes ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The co-development of spinal motor neurons has recently been described in PSC-derived skeletal muscle 3D organoids (Faustino Martins et al, 2020; Mazaleyrat et al, 2020). Interestingly, the data from our model share several aspects of the development of neuromuscular junctions by Faustino Martins et al We observed efficient induction of neuromesodermal progenitor cells expressing SOX2 , Brachyury ( T ) and CDX2 as posterior axis “determinant” (Faustino Martins et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The derivation of skeletal muscle cells from PSC has been demonstrated previously either by transfection or transduction of myogenic transgenes (Albini et al, 2013; Darabi et al, 2012; Goudenege et al, 2012; Kim et al, 2017; Rao et al, 2018; Tedesco et al, 2012; Young et al, 2016) or directed, transgene-free differentiation under controlled growth factors or small molecules stimulation (Borchin et al, 2013; Caron et al, 2016; Chal et al, 2016; Chal et al, 2015; Choi et al, 2016; Shelton et al, 2016; Xi et al, 2017). Recently, more advanced skeletal muscle organoids have been introduced that recapitulate characteristic steps of embryonic neuromuscular co-development (Faustino Martins et al, 2020; Mazaleyrat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%